Membangun Masa Depan: Pentingnya Literasi Keuangan bagi TKI di Malaysia - Miftahul Arifin; Herliani Herliani; Hasnaniah Hasnaniah; Khuzaini Khuzaini (Institut Teknologi dan Bisnis Semarang, 2026)
Digitalization has become a fundamental pillar in the transformation of global labor governance, including for Indonesian Migrant Workers (TKI) in Malaysia, whose numbers reach more than 1.4 million people. This article aims to conduct an in-depth analysis of the urgency of digitalization in improving welfare, legal protection, and access to financial services for TKI in Malaysia through a systematic literature review with a descriptive qualitative approach. The research results show that digitalization has a significant impact in three main domains: (1) legal protection through migtech that bridges the gap between policy and practice, (2) economic efficiency and financial inclusion through fintech and digital wallets, and (3) competency empowerment through digital literacy training. However, various studies also highlight challenges such as suboptimal system privatization, low digital literacy, limited internet access, and the risk of cyber exploitation. The research conclusion emphasizes that digitalization is not merely an additional option but a strategic necessity for migrant workers in Malaysia to build a more independent, protected, and competitive future, with the caveat that a holistic approach involving the government, financial institutions, communities, and the strengthening of bilateral policies is needed.